Modification of the Elevation Plane and Defatting Technique to Create a Thin Thoracodorsal Artery Perforator Flap - Kim, Kyu Nam; Hong, Joon Pio; Park, Chae Ri; Yoon, Chi Sun (Journal of Reconstructive Microsurgery, 2016)
Background Perforator flaps have been used extensively in the field of reconstruction, and the thoracodorsal artery perforator (TDAP) flap is very popular. However, the perforator flap can be relatively bulky in some cases, depending on the defect's location. Thus, several methods have been developed to address this bulkiness, including modification of the flap elevation, application of an ultrathin flap using microdissection, and the defatting technique. However, these methods have various disadvantages, so we developed an adjustable thin TDAP flap using modification of the flap elevation and defatting technique.Methods Between January 2012 and February 2015, 13 patients underwent reconstruction of defects of their upper and lower extremities using TDAP flaps. We measured all the flap dimensions, except for thickness, because it was adjusted for the target defect.Results The mean flap size was 94 cm2 (range: 48–210 cm2), and all flaps were ≤10 cm wide to facilitate primary donor-site closure. Two subjects with a history of diabetes exhibited partial flap loss, so we performed secondary skin graft surgery.Conclusions The TDAP flap elevation was modified at the superficial fascia plane, and the defatting technique was used to adjust the flap volume. This technique provided more natural contours and minimized the need for secondary debulking.
Keywords: thoracodorsal artery perforator flap; superficial fascial plane; defatting procedure